Analisis Anggaran Biaya Produksi Sebagai Alat Perencanaan dan Pengendalian Biaya Produksi (Studi Empiris UD. Bosikan Budidaya Ikan Lele Kepanjen) - Muhammad Azhar Ilham Fauzi; Junaidi Junaidi; Siti Aminah Anwar (Universitas Islam Malang, 2023)
With the increasing consumption of catfish by the public, catfish farming is now also in high demand. As well as supported by existing data from the Ministry of Marine Affairs and Fisheries. A budget is a financial plan designed for future activities in accordance with the objectives of a business. Planning is a process that can produce future plans in making a decision. Control is the most important factor in a business to manage the plan so that it can be fulfilled. Production costs are the price that needs to be paid to convert raw goods into finished goods. Catfish farming is one of the businesses that requires careful planning in terms of its production cost budget. In thi research for the budget and realization can be controlled and for the profits in production I, II and III can already cover expenses in the budget for making the pond and the needs in the budget provided. There are several limitations in this research, namely the production cost budget and this research only uses one object under study.Keywords: Planning and controlling production costs of catfish farming